Analyzing patient perspectives on orthodontic treatment through social media hashtags - Letícia Machado Berretta; Gil Guilherme Gasparello; Evelise Machado de Souza; Giovani Ceron Hartmann; Ewandro Carlos Berretta; Elisa Souza Camargo; Sérgio Aparecido Ignácio; Orlando MotohiroTanaka (PLoS ONE, 2025)
Social media has become a key platform for health-related communication and patient experience sharing. In orthodontics, analyzing patient-generated content on social media helps uncover perceptions, motivations, and concerns related to treatment. Understanding the most commonly reported complaints allows orthodontists to offer solutions, enhancing overall patient satisfaction with treatment The objective of this study is to identify and categorize patient views on orthodontic treatment across social media, providing a broader understanding of global patients’ perspectives. The search was carried out on Instagram and X platforms using the hashtags #braces, #invisalign, #orthodontics, and #orthodontist. Data were collected over a seven-week period without restriction on languages or geographical locations. The qualitative analysis focused involved thematic categorization of posts content, while quantitative analysis used Pearson chi-square tests with Bonferroni-adjusted values, with a significance level of p < 0.05. A total of 18,605 posts were analyzed, with 96.60% (17,971 posts) from Instagram, and 3,4% (634 posts) from X platforms. Of the posts analyzed, 89.52% were made by dentists or dental clinics, 3.86% by dental product companies, and only 0.82% by patients undergoing orthodontic treatment. Five main themes were identified in patient posts: “positive accounts of orthodontic treatment” (40.53%), “enthusiasm about starting treatment” (20.26%), “reports of anxiety due to orthodontic treatment” (19.60%), “complaints and limitations about treatment” (16.34%), and “neutral accounts of orthodontic treatment” (3.27%). No statistically significant associations were found in the nature of content between the two platforms (p > 0.05). Dentists and clinics dominate social media discussions on orthodontics. Among patient-shared content, ‘positive experiences’ were the most frequently mentioned. No significant differences were observed between platforms in the type of posts analyzed.